Shimmering emerging adulthood: in search of the invariant IDEA model for collectivistic countries - Yerofeyeva, Victoria G.; Wang, Pai; Yang, Yisheng; Serobyan, Astghik K.; Grigoryan, Ani K.; Nartova-Bochaver, Sofya K. (Frontiers in Psychology, 2024)
Emerging adulthood is the youth trajectory characterized by self-focus, identity exploration, feeling between adolescence and adulthood, instability, and experimentation. This trajectory was first identified in industrialized individualistic countries with gender equality and technological progress. To measure transition to adulthood, the Inventory of the Dimensions of Emerging Adulthood (IDEA) was created. Although emerging adulthood is considered universal, adaptations of the questionnaire across the 12 countries show different patterns, and its cross-cultural invariance has been underinvestigated. This study tests IDEA in three collectivistic countries – Armenia, China, and Russia. The sample consisted of 868 students (total male – 152, total female – 716) aged 18 to 29 years old. We tested the questionnaire separately in the three countries to check that this model fits, but we failed to prove it. After that we used a factor-analytic approach to find a common version for the three countries. We got a five-factor correlated model in accordance with the theory, but it was reduced from 31 items to 21, and three items moved to other factors. Finally, we provided measurement invariance and reached configural level. To test the narrower facets of factors we used multi-group alignment and found that variances in six parameters differ, mainly in Instability. Despite the difference in the questionnaire items, we proposed a common model for three countries that we called questionnaire IDEA-collectivistic countries (IDEA-CC).